The sacred relationship between marriage, spirituality and healthy aging in Hinduism - Bhattacharyya, Kallol Kumar (Journal of religion, spirituality & aging, 2020)
Marriage is perhaps the most important foundation in human society. In Hinduism, the foundation for marriage is friendship, which is the understanding and the commitment between spouses. Arrange marriage tradition is still considered as the societal norm in India, and is regarded as an event for life. The relationship based on a strong bonding with each other helps the couple to maintain other social relationships in and outside their extended multigenerational family and help spouses to have good physical and mental health in their future life. This influence on their longevity and promotes healthy aging. Marriage, in Hinduism, also considered as the relationship of souls which extends beyond a single life through incarnations. The current literature review discusses the marital relationship from both global and Indian perspective, and explores how the sacred relation between spousal relationship and spirituality influence healthy aging for an individual, in the context of Hinduism.